Education and Mentoring About Cyberbullying Through Law of Information and Electronic Transaction and Islamic Teaching to “Generation Z” - Pinastika Prajna Paramita; Isdiyana Kusuma Ayu; Muntaha Muntaha; Rangga Sa'adillah S.A.P. (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purposes of this mentoring are obtained education about perspective of cyberbullying through Law of Information and Electronical Transaction (A.K.A. UU ITE) and Fatwa MUI Number 24 Year 2017 to students that incidentally called “Generation Z”, a generation that cannot be separated from social media in their lives. The method that used in this mentoring is education in the form of training with model of participatory. It educates more motivating participants actively, not only knowledge transferring but it emphasizes on question and answers, discussion and reflection even though the interest of the students is limit, considering those activities were conducted on Zoom Application. This mentoring was succeeded to change the point of view of students that cyberbullying is a common view, cyber joke is a behaviour that must be avoided because it has an impact on juvenile delinquency, adult crime, domestic violence and suicide. It also creates friendship feud).